Mitoxantrone hydrochloride liposome-based chemotherapy plus rituximab in elderly patients older than 80 years with diffuse large B-cell lymphoma: case report and review of the literature - Pi, Jin-Ping; Liu, Ying; Jin, Jun; Zhang, Wei; He, Xiao-Hui (Frontiers in Medicine, 2025)
BackgroundTreating diffuse large B-cell lymphoma (DLBCL) in patients over 80 years of age remains a significant clinical challenge due to the unfavorable biology of the disease, worse baseline health status (such as cardiac dysfunction), and the toxicities associated with cytotoxic chemotherapy. In this context, attenuated regimens may provide a more favorable risk–benefit profile for elderly DLBCL patients. Mitoxantrone hydrochloride liposome, a liposomal formulation of the synthetic anthracycline anticancer drug, offers several inherent advantages, including reduced cardiotoxicity and targeted delivery to tumor tissue, leading to improved antitumor efficacy and minimized systemic toxicity.Case presentationTherefore, we report a case-series study evaluating the efficacy and safety of mitoxantrone hydrochloride liposome-based chemotherapy plus rituximab in three patients with DLBCL aged over 80 years. Two patients achieved complete metabolic remission (CMR) after treatment with mitoxantrone hydrochloride liposome-based regimens, while one attained CMR after receiving this first-line chemotherapy regimen combined with local radiotherapy. Additionally, the safety profile was acceptable and manageable.ConclusionThese cases suggest that mitoxantrone hydrochloride liposome-based chemotherapy may be effective (all three cases achieved CMR) in very elderly DLBCL patients, warranting further evaluation in larger cohorts.